Authentication of Middle East Mandi Rice at “Cafe Zamrud” Restaurant - Fadzan Rahmidi; Atat Siti Nurani; Karpin Karpin (Universitas Pendidikan Indonesia (UPI), 2023)
This research is motivated by the popularity of the Middle East Mandi Rice dish in the city of Jakarta. Mandi Rice is a typical rice dish from Hadramaut, Yemen which is unique in terms of the use of ingredients, herbs, spices, tools, processing and presentation. This aspect makes it authentic and differentiates Mandi Rice from other Middle Eastern rice dishes. One of the restaurants in the city of Jakarta that serves Mandi Rice is the ”Cafe Zamrud” restaurant. The making of Mandi Rice at the “Cafe Zamrud” restaurant is not necessarily done in an authentic way as is done by the people in their area of origin. The purpose of this study was to determine authentication related to ingredients, seasonings, tools, processing and serving of Mandi Rice at the